Factors affecting E-commerce adoption: A case of Turkey - Birgul Basarir-Ozel; Sona Mardikyan (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
As the number of internet users increases by leaps and bounds, the importance of electronic commerce (e-commerce) channel intensifies among other sales channels. Internet enables products and services to reach large masses in a scalable way. Hence, both academicians and practitioners show great interest in theorizing and understanding the adoption behavior of e-commerce users. For this purpose, factors having impacts on adoption behavior of e-commerce users are investigated within the scope of the study. Our literature review shows that the most influential factors of e-commerce acceptance are perceived usefulness, perceived ease of use and trust. Therefore, an extension of TAM with trust is proposed as the research model. Data on the factors are collected from 186 respondents and analyzed using structural equation modeling (SEM) method to test model validity and hypotheses. This study reveals users' perceptions of usefulness and trust are important factors towards adoption of e-commerce in Turkey. According to our study, Turkish users demand trustworthiness of products and services as well. Moreover, usefulness in means of time and money savings and easy reach of many products and services positively affects adoption. Furthermore, perceived ease of use doesn't directly affect adoption; rather it imposes on e-commerce adoption through perceived usefulness and trust.
Keywords: 650; User Adoption; E-commerce; Technology Acceptance Model (TAM); Trust; Structural Equation Modeling (SEM)